Parenting Strategies for Children with Developmental Delays: A Qualitative Study on Single Parents - Hojjati, Marzieh; Mehdiabadi, Parichehr (Psychological Research in Individuals with Exceptional Needs, 2024)
This study aimed to explore the parenting strategies, support systems, and coping mechanisms employed by single parents of children with developmental delays. A qualitative research design was adopted, involving semi-structured interviews with 23 single parents of children aged 2 to 12 years with diagnosed developmental delays. Participants were recruited through local support groups, online forums, and pediatric clinics. The data collection continued until theoretical saturation was achieved. Thematic analysis, following Braun and Clarke's framework, was used to identify key themes and subthemes within the data. The study identified three main themes: parenting strategies, support systems, and coping mechanisms. Key parenting strategies included routine establishment, positive reinforcement, adaptive techniques, communication strategies, and behavior management. Support systems encompassed family support, professional support, community resources, and financial assistance. Coping mechanisms highlighted were emotional resilience, social networks, personal time management, seeking knowledge, advocacy and empowerment, spirituality, and adaptability. Participants emphasized the importance of structured routines and positive reinforcement in managing their children's needs, while family and professional support were crucial in alleviating caregiving burdens. Effective coping mechanisms were essential for managing stress and maintaining well-being. Single parents of children with developmental delays employ a variety of effective strategies and support systems to navigate their unique challenges. Emotional resilience and social support networks play a critical role in their ability to cope with the demands of caregiving. These findings underscore the need for tailored interventions and resources to support single-parent families, highlighting the importance of flexible services, community resources, and advocacy efforts. Further research should focus on larger, more diverse samples and explore the impact of technological tools in supporting these parents.